Physico-chemical characteristics of red pitaya (Hylocereus polyrhizus) peel - Bakar, Jamilah; Ee, Shu Chee; Syed Muhammad, Sharifah Kharidah; Mat Hashim, Dzulkify; Mohd Adzahan, Noranizan (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Pitaya peel (Hylocereus polyrhizus), which consists approximately 22% of the whole fruit weight, is discarded during processing. Physico-chemical properties of the discarded pitaya peel were determined in order to evaluate its potential for recovery of any value-added materials. The moisture content of the peel was approximately 92.7% and it was low in total soluble solids, protein, ash and fat content. Betacyanin pigment (150.46 ± 2.19 mg/100 g) and pectin (10.8%) were high in the peel. Glucose, maltose and fructose were detected in the peel but not sucrose and galactose. The peel also had very high insoluble and soluble dietary fbre which had exhibited a good ratio of insoluble dietary fbre to soluble dietary fbre (3.8: 1.0).